A Multi-Species Analysis Defines Anaplerotic Enzymes and Amides as Metabolic Markers for Ammonium Nutrition - González-Moro, María Begoña; González-Moro, Itziar; de la Peña, Marlon; Estavillo, José María; Aparicio-Tejo, Pedro M.; Marino, Daniel; González-Murua, Carmen; Vega-Mas, Izargi (Frontiers in Plant Science, 2021)
Nitrate and ammonium are the main nitrogen sources in agricultural soils. In the last decade ammonium (NH4+), a double-sided metabolite, has attracted considerable attention by researchers. Its ubiquitous presence in the plant metabolism and its metabolic energy economy for being assimilated contrast with its toxicity when present in high amounts in the external medium. Plant species can adopt different strategies to maintain NH4+ homeostasis, as the maximization of its compartmentalization and assimilation+ in organic compounds, primarily as amino acids and proteins. In the present study, we report an integrative metabolic response to ammonium nutrition of seven plant species, belonging to four different families: Gramineae (ryegrass, wheat, Brachypodium distachyon), Leguminosae (clover), Solanaceae (tomato) and Brassicaceae (oilseed rape, Arabidopsis thaliana). We use principal component analysis and correlations among metabolic and biochemical data from 40 experimental conditions to understand the whole-plant response. The nature of main amino acids is analysed among species, under the hypothesis that those Asn-accumulating species will show a better response to ammonium nutrition. Given the provision of carbon (C) skeletons is crucial for promotion of the nitrogen assimilation, the role of different anaplerotic enzymes is discussed in relation to ammonium nutrition at a whole-plant level. Among these enzymes, isocitrate dehydrogenase (ICDH) shows to be a good candidate to increase nitrogen assimilation in plants. Overall, metabolic adaptation of different carbon anaplerotic activities is linked with the preference to synthesize Asn or Gln in their organs. Lastly, glutamate dehydrogenase (GDH) reveals as an important enzyme to surpass C limitation during ammonium assimilation in roots, with a disparate collaboration of glutamine synthetase (GS).